Early intervention model of inpatient diabetes care improves glycemia following hospitalization. Issue 4 (4th February 2023) - Kyi, Mervyn; Colman, Peter; Gonzalez, Vicky; Hall, Candice; Cheuk, Nathan; Fourlanos, Spiros
Abstract: Admission to hospital provides an opportunity to optimize long‐term diabetes management, but clinical inertia is common. We previously reported the randomized study of a proactive inpatient diabetes service (RAPIDS), investigating an early intervention model of care and demonstrated improved in‐hospital glycemia and clinical outcomes. This follow‐up study assessed whether proactive care in hospital improved postdischarge HbA1c. In a subgroup of 298 RAPIDS trial participants with type 2 diabetes, age <80 years, and admission HbA1c ≥ 7.0%, diabetes treatment intensification occurred more often in early intervention versus usual care groups (37% vs. 19% [ p  = .001]), adjusted odds ratio 3.2 (95% confidence interval [CI]: 1.7–6.0). There was a greater change in HbA1c in the early intervention group (mean −0.9% [95% CI −1.3 to −0.4]) versus the usual care group (−0.3% [−0.6 to −0.1]), p  = .029. The value of acute care by dedicated inpatient diabetes teams can extend beyond improving inpatient clinical outcomes and can lead to sustained improvement in glycemia. Abstract :